2019
DOI: 10.1096/fj.201901227r
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lacuno‐canalicular network and negative correlation between serum osteocalcin and Cobb angle indicate abnormal osteocyte function in adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is a prevalent spinal deformity occurring during peripubertal growth period that affects 1–4% of adolescents globally without clear etiopathogenetic mechanism. Low bone mineral density is an independent and significant prognostic factor for curve progression. Currently, the cause underlying low bone mass in AIS remains elusive. Osteocytes play an important role in bone metabolism and mineral homeostasis, but its role in AIS has not been studied. In the present study, iliac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
1
9
1
2
Order By: Relevance
“…Similar findings are recently studied by Chen et al who showed that OC was significantly and negatively related to the Cobb's angle [32]. We also found a significant negative OC correlation vs.…”
Section: Resultssupporting
confidence: 92%
“…Similar findings are recently studied by Chen et al who showed that OC was significantly and negatively related to the Cobb's angle [32]. We also found a significant negative OC correlation vs.…”
Section: Resultssupporting
confidence: 92%
“…Similar findings have recently been studied by Chen et al who showed that OC level was significantly lower in the group with the severe AIS (Cobb's angle ≥ 45 • ) compared to the mild subgroup. However, C-terminal telopeptides (CTx) used as a bone resorption marker in this study was insignificantly lower in mild and severe compared to control group [39]. Significant positive correlation of both OC and NTx with Cobb's angle were found by Berglund et al but in the group of patients with scoliosis related to fibrous dysplasia and McCune Albright Syndrome which are related to very high level of bone turnover [40].…”
Section: Discussioncontrasting
confidence: 45%
“…A visual example of this scanning protocol and resulting images can be seen in To determine the optimal beam energy, three samples of trabecular bone were scanned at three beam energies: 55, 70, and 90kVp. These samples used for beam energy optimization originated from a separate study [38]; however, they were also human bone biopsies from the iliac crest and were considered to be comparable with our biopsy group. We aimed to maximize the image signal-to-noise ratio (SNR) just as previous studies relating to other anatomical bone sites had done [39].…”
Section: Image Acquisitionmentioning
confidence: 99%